Entrepreneurial finance in Europe and the Russian war against Ukraine - Helmut Kraemer-Eis; Joern Block; Antonia Botsari; Frank Lang; Solvej Lorenzen; Walter Diegel (The Journal of Technology Transfer, 2024)
Prior research has investigated how the prices of stocks and commodities as well as inflation levels have been affected by the Russian war against Ukraine. So far, however, we know little about the impacts of the war on the entrepreneurial finance sector. Prior research on the effects of unexpected exogenous crisis events on entrepreneurial finance suggests a strong negative impact on new and follow-on funding for entrepreneurial ventures. Our study regards the Russian war against Ukraine as an unexpected exogenous crisis event and explores its impact on the entrepreneurial finance sector. It goes beyond a mere sentiment and impact analysis and also explores the underlying reasons and mechanisms as well as potential response and coping strategies employed by entrepreneurial finance investors. Based on two surveys of European venture capital (VC) and private equity (PE) investors, we find that the war had a strong negative impact on the two types of investors and their respective funds. Both VC and PE investors report more risk-aversion of limited partners (LPs) and LPs leaving the market as important challenges resulting in an overall lower willingness of LPs to invest. This applies in particular to banks, insurance funds, and pension funds. On the portfolio firm level, securing equity financing and maintaining liquidity were considered pressing issues. Overall, the situation seems to be more difficult for portfolio companies of VC as compared to PE investors. For the former, the financing- and liquidity-related issues seem to be more existential and survival-threatening. Responding to these challenges, both VC and PE investors altered their industry focus and put more emphasis on entrepreneurial experience. Financial investment selection criteria such as financial valuation, profitability, and cash- as well as revenue-generating capacity also increased in importance. Again, differences between VC and PE investors exist. Our study has implications for entrepreneurial finance theory and practice and concludes with an agenda for research on the impacts of the Russian war against Ukraine on entrepreneurial finance.
Keywords: G24; M13; N44; 600; Entrepreneurial finance; Russian war against Ukraine; Venture capital; Private equity; Exogeneous crisis